Trainings to improve students’ understanding in fiqh of muamalah, English, and Arabic at Muhammadiyah Islamic Boarding School, Ponorogo - Muhammad Faqih Nidzom; Henri Shalahuddin; Ahmad Farhan Nasution Nasution; Abditya Saputra; Aidil Putra Syurbakti; Alfian Amrullah; Allan Muhammad; Aula Umam Rizky; Faisal Majid Abdullah; Faris Alfi Fauzi; M. Adil Alwi Zaim; Rizvan Falah Kamil; Vandeber Oktavianos (Universitas Muhammadiyah Malang, 2025)
This training is designed to enhance the understanding of students regarding the Fiqh of Muamalah and to improve their English and Arabic language skills. The Fiqh of Muamalah curriculum covers fundamental principles of interaction and transactions according to Islamic law, aiming to equip students with the ability to understand, analyze, and apply fiqh principles in daily life contexts. The English and Arabic language enhancement program is intended to strengthen students' communication skills in foreign languages, which serve as essential assets for facing global challenges. The teaching methods include interactive lectures, group discussions, practical muamalah simulations, and intensive language practice through dialogues and presentations. This program is expected to produce students who are not only proficient in understanding the Fiqh of Muamalah but also competent in English and Arabic, preparing them to be an outstanding generation in religious knowledge and language skills in the globalization era.